073. Tamoxifen - Associated Hirsutism: An Usual Side Effect in A 52-Year-Old Women with Malignant Neoplasm of Left Breast - Asri, Asri; Abidin, Zainal (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical EducationDO - 10.24843/JBN.2024.v08.is02.p073, 2024)
Background : Hirsutism is a condition characterized by growth of excessive male-pattern (i.e., face, chest, abdomen, lower back, upper arms, and thighs) hair  in women. The prevalence of hirsutism has been reported to be between 5% and 15% in women and can be caused by various factors, including the use of medications such as Tamoxifen. The modified Ferriman-Gallwey (mFG) score is the preferred and most widely used method for scoring excess terminal hair in the assessment of hirsutism. This case report aims to explore the relationship between Tamoxifen use and the development of hirsutism, as well as to discuss the potential mechanisms involved. Case :  A 52-year-old female patient was diagnosed with a left breast tumor and underwent neoadjuvant chemotherapy followed by treatment with Tamoxifen 10 mg daily for six months. After treatment, the patient reported abnormal hair growth on her face, chest, arms, and legs. Conclusion: The use of Tamoxifen may contribute to the development of hirsutism in some patients. It is important to monitor these side effects and consider appropriate management strategies for patients experiencing hirsutism related to treatment.